2015
DOI: 10.1111/ajt.13107
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Individual and Combined SNPs in Genes Related to Innate Immunity and Incidence of CMV Infection in Seropositive Kidney Transplant Recipients

Abstract: In this study, we assessed the association between single-nucleotide polymorphisms (SNPs) in seven candidate genes involved in orchestrating the immune response against cytomegalovirus (CMV) and the 12-month incidence of CMV infection in 315 CMVseropositive kidney transplant (KT) recipients. Patients were managed either by antiviral prophylaxis or preemptive therapy. CMV infection occurred in 140 patients (44.4%), including 13 episodes of disease. After adjusting for various clinical covariates, patients harbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 43 publications
(75 reference statements)
3
39
0
Order By: Relevance
“…Among pregnant women, the low genotypic variability within TLR2 and TLR4 SNPs seems to be the important cause of the lack of any associations with HCMV infection. Similarly to our study, almost the same frequencies of distinct genotypes in both TLR2 2258 G > A and TLR4 896 G > A SNPs were determined in patients with transplants, with and without clinical signs of HCMV infection [50]. Regarding the outcomes presented in this report, TLR9 2848 G > A SNP seems to be the major polymorphism, contributing to HCMV infection in pregnant women during pregnancy.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Among pregnant women, the low genotypic variability within TLR2 and TLR4 SNPs seems to be the important cause of the lack of any associations with HCMV infection. Similarly to our study, almost the same frequencies of distinct genotypes in both TLR2 2258 G > A and TLR4 896 G > A SNPs were determined in patients with transplants, with and without clinical signs of HCMV infection [50]. Regarding the outcomes presented in this report, TLR9 2848 G > A SNP seems to be the major polymorphism, contributing to HCMV infection in pregnant women during pregnancy.…”
Section: Discussionsupporting
confidence: 85%
“…In turn, the fetuses were diagnosed as congenitally infected with HCMV only on the basis of ultrasound markers and on the presence of HCMV DNA in their body fluids, since the diagnostics towards the infection is not routinely performed in pregnant women. Considering the role of TLR9 SNP in HCMV infection, the TT homozygotic status in TLR9 -1237 T > C SNP was reported to have been correlated with a decreased risk of the infection in HCMV-seropositive kidney transplant recipients [50]. In recipients of allogeneic hematopoietic stem cell transplants, the HCMV infection occurred significantly more frequently among carriers of minor C allele in TLR9 -1237 T > C, as compared to the patients, carrying the T allele [51].…”
Section: Discussionmentioning
confidence: 99%
“…This is however different from the dominant model of inheritance seen in HCV studies, [11][12][13]15 suggesting that the two viruses may have different interactions with IFN-λ-driven immune responses. However, unlike in the case of CMV studies discussed above, [47][48][49][50][51] all three HIV studies [72][73][74] show that the minor alleles are non-beneficial, similar to the observations in chronic HCV infections. 15 In summary, it is evident that IFNL SNPs do associate with HIV replication and disease progression, even though in an ethnicity-specific manner.…”
Section: Hepatitis B Virussupporting
confidence: 58%
“…These results are indeed very interesting and sound, but the paradoxical findings of the five groups in terms of the model of inheritance of IFNL SNPs raise some questions. Although two groups showed that their results fit best with a recessive model of inheritance of IFNL SNPs 50,51 in affecting CMV replication/retinitis wherein minor homozygosity was non-beneficial, the other three studies show an opposite trend where the minor allele had a beneficial effect against CMV replication in both patients and cell culture experiments, involving either dominant 47,48 or recessive models of inheritance. 49 In stark contrast, a dominant model of inheritance (of the non-beneficial IFNL SNP minor allele) has consistently given the best explanation on the observed phenotypes in association studies with both spontaneous clearance and IFN-based treatment response in chronic HCV infections.…”
Section: Cytomegalovirus Cytomegalovirus (Cmv) Is a Herpes Virus Thamentioning
confidence: 98%
“…Genotypic analyses of transplant recipients, and in some instances that of donors, may also help determine the risk of active CMV infection and invasive disease. Some single nucleotide polymorphisms (SNPs) in genes encoding pattern recognition molecules and receptors (mannose‐binding lectin, ficolin‐2, toll‐like receptors 2, 4, and 9, dendritic cell‐specific ICAM3‐grabbing non‐integrin, and chemokine receptor 5), cytokines and chemokines (interleukin‐12, interleukin‐10, interferon‐γ, interferon‐λ3 ‐IL28B‐, and monocyte chemoattractant protein 1), and immune regulatory membrane‐associated proteins (human programmed death‐1) appear to be associated with a higher risk of developing active CMV infection, CMV end‐organ disease, or both, in allogeneic stem cell and SOT transplantation settings [Loeffler et al, ; Cervera et al, , ; Kijpittayarit et al, ; Hoffmann et al, , ; Mezger et al, ; Brown et al, ; de Rooij et al, ; Mitsani et al, ; Kang et al, ; Bravo et al, ; Egli et al, ; Corrales et al, ; Fernández‐Ruiz et al, ; Manuel et al, ]. These SNPs may also have an impact on the dynamics of CMV replication within episodes of active CMV infection [Corrales et al, ].…”
Section: Introductionmentioning
confidence: 99%